Microbial membrane lipid adaptations to high hydrostatic pressure in the marine environment - Tamby, Anandi; Sinninghe Damsté, Jaap S.; Villanueva, Laura (Frontiers in Molecular Biosciences, 2023)
The deep-sea is characterized by extreme conditions, such as high hydrostatic pressure (HHP) and near-freezing temperature. Piezophiles, microorganisms adapted to high pressure, have developed key strategies to maintain the integrity of their lipid membrane at these conditions. The abundance of specific membrane lipids, such as those containing unsaturated and branched fatty acids, rises with increasing HHP. Nevertheless, this strategy is not universal among piezophiles, highlighting the need to further understand the effects of HHP on microbial membranes. Challenges in the study of lipid membrane adaptations by piezophiles also involve methodological developments, cross-adaptation studies, and insight into slow-growing piezophiles. Moreover, the effects of HHP on piezophiles are often difficult to disentangle from effects caused by low temperature that are often characteristic of the deep sea. Here, we review the knowledge of membrane lipid adaptation strategies of piezophiles, and put it into the perspective of marine systems, highlighting the future challenges of research studying the effects of HHP on the microbial lipid composition.